Impedance spectroscopy studies on lead free Ba1-xMgx(Ti0.9Zr0.1)O3 ceramics. (June 2018) - Ben Moumen, S.; Neqali, A.; Asbani, B.; Mezzane, D.; Amjoud, M.; E.Choukri,; Gagou, Y.; El Marssi, M.; Luk'yanchuk, Igor A.
Abstract: Ba1-x Mgx (Ti0.9 Zr0.1 )O3 (x = 0.01 and 0.02) ceramics were prepared using the conventional solid state reaction. Rietveld refinement performed on X-ray diffraction patterns indicates that the samples are tetragonal crystal structure with P4mm space group. By increasing Mg content from 1 to 2% the unit cell volume decreased. Likewise, the grains size is greatly reduced from 10 μm to 4 μm. The temperature dependence of dielectric constants at different frequencies exhibited typical relaxor ferroelectric characteristic, with sensitive dependence in frequency and temperature for ac conductivity. The obtained activation energy values were correlated to the proposed conduction mechanisms. Graphical abstract: Highlights: Structural, impedance spectroscopy and dielectric properties of Mg2+ modified BaTi0.9Zr0.1O3 are explored. Important room temperature dielectric constant was obtained for x = 0.01. All the samples showed diffuse relaxor ferroelectric feature.